Efficacy of using Intravaginal Misoprostl in mid-trimester missed abortion (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Termination of missed abortion in the second trimester by suction evacuation is more traumatic than in early pregnancy. Misoprostl is effective in first and second trimester abortions. Vaginal route being superior to oral. Objectives: The study was carried out to evaluate the effectiveness and safety of vaginal Misoprostl in the management of second trimester missed abortion. Methods: This prospective study was carried out in the department of Obstretrics and Gynaecology, Dhaka Medical College Hospital from January 2004 to December 2004. A total 50 missed abortion patients were randomly selected. After required investigations Tab Misoprostol 200 ug was introduced per vagina in the posterior fornix which was repeated every four hours. The incidence of complete expulsion and side effect was examined. The patient who did not respond to Misoprostol, Oxytocin infusion was given to them after 6 hours of the last doses of Misoprostol. If the patient failed to respond, surgical evacuation was attempted. Ultrasonogram was done after 12 hours to confirm complete abortion. Results: Among the 50 cases 38 (76%) had gestation age within the range of 13?24 weeks. Twenty five (50%) cases required only Misoprostol for expulsion of product of conception with range of 1?4 doses. Eight (16%) required misoprostol with oxytocin drip & 17 (34%) required surgery even after misoprostol & oxytocin. The induction-expulsion interval of 25 (50%) cases was 11±4 in 25 women who were given Tab Misoprostol only. Forty three (86%) had no side effects & well-tolerated with the drug. Only Misoprostol is 09 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 required in gestational age group of 21?24 weeks (64.3%) & 25?28 weak (66.7%). Misoprostol was successfully used in most Nulliparous women (64.7%) & Primiparous women (42.9%). Conclusion: The second trimester missed abortion termination by srgical evacuation is traumatic and complications are more. If Tab Misoprostol proves safe and effective a large number of patients will be benefited and will escape from surgical intervention and complications. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22897 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014